Factors associated with resection volume and reoperation rates in breast-conserving surgery - Karhunen-Enckell, Ulla; Salminen, Annukka; Tolonen, Teemu; Joukainen, Sarianna; Aaltonen, Riitta; Norja, Heikki; Repo, Heli; Korpinen, Katarina; Metsola, Hanna; Lesonen, Timo; Kronqvist, Pauliina; Luukkaala, Tiina; et al. (Elsevier, 2026)
Background
Achieving tumor-free margins without unintentional tissue loss is essential in breast-conserving surgery (BCS). Calculated resection ratio (CRR) and tumor eccentricity measuring tumor displacement from the specimen center have been proposed as complementary quality metrics to reoperation and mastectomy rates. The objective of this study was to identify factors influencing CRRs and reoperations in BCS.
Methods
The prospective, multi-center FIBRATIO study included 206 women undergoing unilateral BCS for invasive cancer and/or ductal carcinoma in situ across five Finnish centers. Tumor, specimen, and breast volumes were measured radiologically and histopathologically. CRRs, defined as total resection volume (TRV) divided by optimal resection volume, were calculated both radiologically (CRRrad) and histologically (CRRpat). Eccentricity and relative eccentricity (adjusted for tumor size) were also assessed. Associations with clinical and imaging variables, and reoperations were analyzed using multivariable analyses.
Results
Median CRRrad was 2.3 [interquartile range (IQR) 1.5–3.7] and CRRpat 2.4 (IQR 1.4–3.7). Relative eccentricity was 1.0 (IQR 0.5–2.0), higher in smaller tumors and correlated with CRRs. Reoperation occurred in 14% of patients and was associated with larger lesion size and lower CRRs. High CRRs were associated with large breast volume, non-dense breasts, and non-palpable tumors. CRRs decreased with increasing tumor size. Tumor spiculation was associated with higher CRRrad. Statistically significant inter-surgeon and inter-center variability in CRRs and reoperation rates was observed.
Conclusions
BCS is associated with variable and often excessive resection of healthy tissue. Identifying patients at risk for over-resection may improve surgical planning. Incorporating CRR into quality metrics alongside reoperation and mastectomy rates could enhance benchmarking.